2015
DOI: 10.1186/s12885-015-1977-3
|View full text |Cite
|
Sign up to set email alerts
|

High EGFR protein expression and exon 9 PIK3CA mutations are independent prognostic factors in triple negative breast cancers

Abstract: BackgroundTriple negative breast cancers (TNBC) are a more aggressive subset of breast cancer. A better understanding of its biology could allow the rational development of targeted therapies.MethodsWe extensively analyzed the EGFR/PI3K/PTEN axis in a large, homogeneous population of TNBC to help defining the putative role of anti-EGFR and -PI3K targeted therapies in this setting. EGFR gene amplification, EGFR protein expression, PIK3CA and PTEN gene alterations (two members of EGFR downstream pathways) and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…EGFR gene amplification is a frequent phenomenon occurring in many tumors, such as lung cancers [ 26 ], gastric cancer [ 27 , 28 ], and breast cancers [ 29 , 30 ]. Furthermore, high polysomy or gene mutation has been reported to play a role in EGFR overexpression in non-small-cell lung cancers and in breast cancer [ 31 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…EGFR gene amplification is a frequent phenomenon occurring in many tumors, such as lung cancers [ 26 ], gastric cancer [ 27 , 28 ], and breast cancers [ 29 , 30 ]. Furthermore, high polysomy or gene mutation has been reported to play a role in EGFR overexpression in non-small-cell lung cancers and in breast cancer [ 31 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…E545K and H1047R mutations account for 90% of these mutations. PIK3CA mutations are associated with decreased survival in many cancers, but their impact on HNSCC has so far been limited to serving as a marker of late stage disease (14)(15)(16). Interestingly, PIK3CA, like P120CTN, is affected by tobacco smoke, the primary risk factor for HNSCC.…”
Section: Introductionmentioning
confidence: 99%
“…usage as a consolidation or intensification therapy. In this context, the results of CIREL will also improve our understanding of LP-irinotecan TACE used in clinical settings which are less commonly studied such as in chemotherapy-naive patients, only reported on in a few studies [ 10 , 31 ]. With a bigger sample size and in relation to these categories, effectiveness outcomes like overall survival and (hepatic) progression-free survival will be reported in the final analysis.…”
Section: Discussionmentioning
confidence: 99%
“…PES (grade 1) is also the most common adverse events (AE) by far in this interim analysis. While the number of reported grade 1 and grade 2 AEs varied highly, most studies reported none [ 36 , 41 , 42 ]] or below 10% [ 10 , 27 , 31 , 43 ] adverse events of grade 3 and 4. This is in line with what was observed in CIREL with 10% of grade 3 reported adverse events and only 4% of grade 4 in this interim analysis.…”
Section: Discussionmentioning
confidence: 99%